Robust and efficient quantum optimal control of spin probes in a complex (biological) environment. Towards sensing of fast temperature fluctuations - Konzelmann, Philipp; Rendler, Torsten; Bergholm, Ville; Zappe, Andrea; Pfannenstill, Veronika; Garsi, Marwa; Ziem, Florestan; Niethammer, Matthias; Widmann, Matthias; Lee, Sang-Yun; Neumann, Philipp; Wrachtrup, Joerg (IOP PUBLISHING LTD, 2018)
We present an optimized scheme for nanoscale measurements of temperature in a complex environment using the nitrogen-vacancy center in nanodiamonds (NDs). To this end we combine a Ramsey measurement for temperature determination with advanced optimal control theory. We test our new design on single nitrogen-vacancy centers in bulk diamond and fixed NDs, achieving better readout signal than with common soft or hard microwave control pulses. We demonstrate temperature readout using rotating NDs in an agarose matrix. Our method opens the way to measure temperature fluctuations in complex biological environment. The used principle is universal and not restricted to temperature sensing.
Keywords: NITROGEN-VACANCY CENTERS; THERMOMETRY; FLUORESCENCE